Synergistic Molecular Effect of BDNF, ApoE and MTHFR in inducing Depression in Alzheimer’s Disease - Atif Amin, Baig; Mohd Adzim Khalili, Rohin; Ahmad Zubaidi, A.latif; Nordin, Simbak (2018)
Alzheimer’s disease is genetically and pathophysiologically linked to depression. Various studies have been formulated on AD patients with depression and AD patients without depression. Genes like BDNF, ApoE and MTHFR have a significant role in depressed individuals causing the development of Alzheimer’s disease. The frequency of each gene marks the onset of Alzheimer’s disease. Single Nucleotide Polymorphisms in each specific gene show the increased risks of developing Alzheimer’s disease in depressed individuals. Amyloid Senile plaques and neurofibrillary tangles are caused more often in a depressed individual leading to AD. Development of antidepressants may lead to the correction and diminishing of AD in depressed individuals.